Improving high school students’ speaking skill through role play strategy: A classroom action research - Sayow, Eiren Lady Marchela; Marsevani, Maya (Universitas Muhammadiyah Malang, 2024)
This study utilized Classroom Action Research and was carried out during a teaching internship in a Junior High School in Batam, Indonesia involving 20 eighth-grade students. The objective of the study is to investigate the impact of implementing the Role Play Strategy on students' attitude, interest, and effort in practicing English speaking skills. The research was structured into distinct stages, including planning, action, observation, and reflection. The research instruments used were observation, pre-test, and post-test. The students were initially observed during their English lessons, after which the pre-test and post-test were administered to evaluate the improvement in their speaking skills. A rubric was devised to assess the students' speaking skills across various aspects. The post-test results revealed a significant improvement in the students' scores compared to the pre-test, demonstrating the effectiveness of the Role Play Strategy in enhancing their speaking abilities. The students' average score for the pre-test was 67.85 points, while their average score for the post-test was 73 points after the implementation of Role Play. Therefore, it can be concluded that the use of Role Play Strategy in classroom instruction is an effective approach for promoting students' speaking skills. The result suggests that the teachers should use creative and modified teaching materials to improve students' curiosity in learning English.